Implementation of Rabies Control and Prevention Policy in Tomohon City - Pontoh, Vinzentia Varina Grace; Masengi, Evi; Dilapanga, Abdul Rahman (Technium Social Sciences Journal, 2021)
This study aims to uncover, describe, analyze, and implement the control and control policies for rabies in Tomohon City. This study uses a qualitative approach with data collection techniques; interviews, observations and documentation. The data analysis technique used is an interactive model analysis from Miles and Huberman, which includes; data collection, data reduction, data display and conclusion/verification, while the validity of the data was tested using credibility, dependability, transfer and confirmability. The conclusions of this study are 1. The policy of the rabies control and prevention program implemented by the Tomohon City Agriculture and Fisheries Service as a whole has not been appropriately implemented. The indicators illustrate this studied: policy actions, factors influencing policy implementation, and public responses to rabies control and control. 2. The study results describe that the Department of Agriculture and Fisheries of Tomohon City has not been able to implement all policy actions in controlling and controlling rabies. 3. The study results also show that the bureaucratic structure, communication, resources, and disposition (attitude of implementers) as influencing factors do not support the implementation of rabies control and control policies. 4. As a result of the lack of socialization of the rabies control and prevention policy, some people do not support the implementation of this policy.